Structure, inheritance, and transcriptional effects of Pce1, an insertional element within Phanerochaete chrysosporium lignin peroxidase gene lipI. - Gaskell, J (1995)
A 1747-bp insertion within a lignin peroxidase allele of Phanerochaete chrysosporium BKM-F-1767 is described. Pce1, the element, lies immediately adjacent to the fourth intron of lip12. Southern blots reveal the presence of Pce1-homologous sequences in other P. chrysosporium strains. Transposon-like features include inverted terminal repeats and a dinucleotide (TA) target duplication. Atypical of transposons, Pce1 is present at very low copy numbers (one to five copies), and conserved transposase motifs are lacking. The mutation transcriptionally inactivates lip12 and is inherited in a 1:1 Mendelian fashion among haploid progeny. Thus, Pce1 is a transposon-like element that may play a significant role in generating ligninolytic variation in certain P. chrysosporium strains.